2016
DOI: 10.1088/1475-7516/2016/11/033
|View full text |Cite
|
Sign up to set email alerts
|

The role of Dark Matter sub-halos in the non-thermal emission of galaxy clusters

Abstract: Abstract. Annihilation of Dark Matter (DM) particles has been recognized as one of the possible mechanisms for the production of non-thermal particles and radiation in galaxy clusters. Previous studies have shown that, while DM models can reproduce the spectral properties of the radio halo in the Coma cluster, they fail in reproducing the shape of the radio halo surface brightness because they produce a shape that is too concentrated towards the center of the cluster with respect to the observed one. However, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…The required values of the normalization of the DM model for the 9 and 43 GeV cases are B × σ v = 6 × 10 −25 cm 3 s −1 and 4 × 10 −24 cm 3 s −1 respectively. Comparing these numbers with the best fit values for the annihilation cross section found in the Galactic center [27], we found that the required value of the substructures boosting factor is of the order of 30-50 for the two models with 9 and 43 GeV mass, that is reasonable for galaxy clusters [3,29,7]. If instead the values of the cross section are fixed to the upper limits found in Dwarf Galaxies studies with Fermi-LAT [30] or in CMB studies with Planck [31], we found that the boosting factor should take values of the order of 150-300, that are more difficult but not impossible to have in galaxy clusters [32,7].…”
Section: Pos(heasa2017)006mentioning
confidence: 55%
See 2 more Smart Citations
“…The required values of the normalization of the DM model for the 9 and 43 GeV cases are B × σ v = 6 × 10 −25 cm 3 s −1 and 4 × 10 −24 cm 3 s −1 respectively. Comparing these numbers with the best fit values for the annihilation cross section found in the Galactic center [27], we found that the required value of the substructures boosting factor is of the order of 30-50 for the two models with 9 and 43 GeV mass, that is reasonable for galaxy clusters [3,29,7]. If instead the values of the cross section are fixed to the upper limits found in Dwarf Galaxies studies with Fermi-LAT [30] or in CMB studies with Planck [31], we found that the boosting factor should take values of the order of 150-300, that are more difficult but not impossible to have in galaxy clusters [32,7].…”
Section: Pos(heasa2017)006mentioning
confidence: 55%
“…where i is the index referring to the output product (i.e. electrons/positrons or photons), σ v is the thermally-averaged WIMP annihilation cross-section, the index f labels annihilation final states with branching ratios B f , the production spectra (dN f i )/(dE) can be calculated using the DarkSusy package [11], and B is a multiplicative boosting factor produced by the effect of smaller DM substructures [12,7]. In the following we will use the neutralino as a candidate WIMP, but the results can be valid for a generic WIMP having similar properties.…”
Section: The Dm Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In the above analysis, we did not include any substructure contributions. Simulations show that some substructures exist in dark matter profile which can boost the annihilation signals [35,36,37]. However, no observational evidence of these substructures is found.…”
Section: Spectral Data Fittingmentioning
confidence: 95%
“…Therefore, the parametrization can be applied and the corresponding boost factors are 35 and 30 respectively. As discussed in 32 , the boost factor of the order are standard values for galaxy clusters. By taking these boost factors, we can calculate the direct emission flux for each galaxy cluster by , where D is the distance of the galaxy cluster.…”
Section: Methodsmentioning
confidence: 99%